Prinsip Pertanggungjawaban Pidana bagi Influencer yang Mempromosikan Produk Kosmetik Ilegal di Indonesia - milda atia; Sulistina (Cv. Kalimasada Group, 2026)
The prevalence of digital promotions for illegal cosmetics involving influencers raises legal issues regarding criminal liability for promoting products that potentially endanger consumers. This study aims to analyze the principles of criminal liability for influencers promoting illegal cosmetic products in Indonesia, as well as to examine the types of offenses and legal basis for their imposition. The research method used is normative legal research with a statutory and conceptual approach, through an analysis of relevant regulations such as the Consumer Protection Law, the Electronic Information and Transactions Law, and health provisions. The results indicate that influencers can be held criminally liable if proven guilty, whether intentional or negligent, especially if they knew or reasonably suspected that the product being promoted did not have a distribution permit. Furthermore, influencers' involvement in the promotional distribution chain strengthens their position as legal subjects subject to criminal sanctions. The implications of this study emphasize the importance of improving legal literacy for influencers and the need for strengthened government oversight of digital promotions to protect consumers from the risks of using dangerous illegal cosmetics.